Cellular respiration energy for life - Cochran, Peter; Human Relations Media, inc. ([Pleasantville, NY] : HRM Video, 1995)
(Producer) Special effects and graphics demonstrate how cells convert nutrients into energy. The program describes the crucial steps of aerobic and anerobic respiration, the Krebs cycle, and the electron transport chain, as well as the concepts of kilocalories, potential energy, and kinetic energy.
Author & producer, Peter Cochran ; consultant, Bill Surver.
Keywords: Cell Respiration -- physiology -- videocassettes